2022
DOI: 10.1021/acsomega.2c02291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Slight Changes in Aromaticity through Electronic and Density Functional Reactivity Theory-Based Descriptors

Abstract: Aromaticity is a useful tool to rationalize the structure, stability, and reactivity in several compounds. Although aromaticity is not directly an observable, it is well accepted that electronic delocalization around the molecular ring is a key stabilizing feature of aromatic compounds. This contribution presents a systematic evaluation of the capability of delocalization and reactivity criteria to describe aromaticity in a set of fluorinated benzenes. The aromaticity indices are compared with quantities obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The fulvenization process serves as a methodology for quantifying the aromaticity of the benzene derivatives. An example is found in the persubstituted benzenes when hydrogen atoms are replaced by fluorine atoms, which presents a reduction in its aromatic character (25.09 kcal·mol –1 ), in agreement with previous studies applying the magnetic criteria and information-theoretic-based indicators . A reduction in aromaticity is also observed when hydrogens are replaced by chlorine, cyano, and hydroxyls, whose values are 30.56, 26.20, and 26.18 kcal·mol –1 , respectively (Figure S1 in the Supporting Information) .…”
Section: Results and Discussionsupporting
confidence: 89%
“…The fulvenization process serves as a methodology for quantifying the aromaticity of the benzene derivatives. An example is found in the persubstituted benzenes when hydrogen atoms are replaced by fluorine atoms, which presents a reduction in its aromatic character (25.09 kcal·mol –1 ), in agreement with previous studies applying the magnetic criteria and information-theoretic-based indicators . A reduction in aromaticity is also observed when hydrogens are replaced by chlorine, cyano, and hydroxyls, whose values are 30.56, 26.20, and 26.18 kcal·mol –1 , respectively (Figure S1 in the Supporting Information) .…”
Section: Results and Discussionsupporting
confidence: 89%
“…The addition of the second benzyl moiety in the linker section of the EADR04 molecule improves electron delocalization in the molecule, which in turn increases its electronic and thermal stability. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…Among numerous available descriptors, the nucleus-independent chemical shift (NICS(1) zz , NICS(1.5) zz ), 23 and para -delocalization index (PDI) 24 were selected to study the aromaticity of 5-phenylhydantoins (for more details see Computational details). Based on the results of a recent evaluation of aromaticity descriptors, 25 it was shown that these two descriptors have an excellent correlation with the ring current strength (RCS), value used as a referent. The applicability of the selected DFT method was tested on the benzene molecule, and the obtained values of PDI and NICS(1) zz are in excellent agreement with the literary ones.…”
Section: Resultsmentioning
confidence: 99%